2001
DOI: 10.7589/0090-3558-37.1.138
|View full text |Cite
|
Sign up to set email alerts
|

Aleutian Mink Disease Parvovirus in Wild Riparian Carnivores in Spain

Abstract: Serious declines in populations of native European mink (Mustela lutreola) have occurred in Europe. One responsible factor may be infectious diseases introduced by exotic American mink (Mustela vison). In order to investigate a possible role for Aleutian mink disease parvovirus (ADV), we surveyed native riparian carnivores and feral American mink. When serum samples from 12 free-ranging European and 16 feral American mink were tested, antibodies to ADV were detected from three of nine European mink. ADV DNA wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
90
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 18 publications
2
90
0
3
Order By: Relevance
“…with American mink and has played a significant role in reducing the European mink population [7,16]. However, there are still no persuasive arguments that could definitively confirm or rule out the possibility of the circulation of AMDV between populations of farmed and free-living animals.…”
Section: Introductionmentioning
confidence: 99%
“…with American mink and has played a significant role in reducing the European mink population [7,16]. However, there are still no persuasive arguments that could definitively confirm or rule out the possibility of the circulation of AMDV between populations of farmed and free-living animals.…”
Section: Introductionmentioning
confidence: 99%
“…Free-ranging American mink populations are infected with the Aleutian mink disease virus (AMDV) across Canada [1][2][3][4][5] and in several European countries [6][7][8][9]. The occurrence of natural infection with or exposure to AMDV in a few members of the Mustelidae family (e.g., European mink, ferrets, polecats, stone martens, pine martens, Eurasian otters), and other carnivores (striped skunks, common genets, raccoons, foxes) has also been reported [6,8,[10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…It appears that North American river otters can be exposed to AMDV (Wells et al 1989;Mañ as et al 2001;Farid 2013); however, it remains to be confirmed whether otters can mount an immune response (i.e., exhibit AMDV antibodies), and express clinical symptoms of disease (Kenyon et al 1978;Wells et al 1989;Farid 2013). Nevertheless, our finding of no evidence of AMDV in otters in a location with known infection in mink may be indicative of barriers to spread between mink and otter.…”
mentioning
confidence: 72%
“…Wildlife other than American mink can become infected with or exposed to AMDV, including striped skunk (Mephitis mephitis), ermine (Mustela erminea), European mink (Mustela lutreola), raccoon dog (Nyctereutes procyonoides), and raccoon (Procyon lotor) (Alexandersen et al 1985;Mañ as et al 2001;Pennick et al 2007;Farid 2013). Given demonstrated global problems with mink farm biosecurity (Bonesi and Palazon 2007;Bowman et al 2007), there is potential for mink farms to be sources of cross-species spillover of AMDV (Nituch et al 2011(Nituch et al , 2012.…”
mentioning
confidence: 99%
See 1 more Smart Citation